Answer:
-1/6
Step-by-step explanation:
-1/2 + ( 3/4 x 4/9)
PEMDAS says parentheses first
Rearranging the fractions
-1/2 + ( 3/9 x 4/4)
-1/2 + (1/3*1)
-1/2 + 1/3
Getting a common denominator of 6
-1/2 *3/3 + 1/3 *2/2
-3/6+2/6
-1/6
Answer: The value of g(x) is x+3.
Step-by-step explanation:
Since we have given that
![h(x)=f\circ g(x)](https://tex.z-dn.net/?f=h%28x%29%3Df%5Ccirc%20g%28x%29)
Here,
![h(x)=\sqrt{x+5}\\\\and\\\\f(x)=\sqrt{x+2}](https://tex.z-dn.net/?f=h%28x%29%3D%5Csqrt%7Bx%2B5%7D%5C%5C%5C%5Cand%5C%5C%5C%5Cf%28x%29%3D%5Csqrt%7Bx%2B2%7D)
We need to find the value of g(x):
![f(x)=\sqrt{x+2}\\\\f(g(x))=\sqrt{g(x)+2}\\\\h(x)=\sqrt{g(x)+2}\\\\\sqrt{x+5}=\sqrt{g(x)+2}\\\\x+5=g(x)+2\\\\g(x)=x+5-2=x+3](https://tex.z-dn.net/?f=f%28x%29%3D%5Csqrt%7Bx%2B2%7D%5C%5C%5C%5Cf%28g%28x%29%29%3D%5Csqrt%7Bg%28x%29%2B2%7D%5C%5C%5C%5Ch%28x%29%3D%5Csqrt%7Bg%28x%29%2B2%7D%5C%5C%5C%5C%5Csqrt%7Bx%2B5%7D%3D%5Csqrt%7Bg%28x%29%2B2%7D%5C%5C%5C%5Cx%2B5%3Dg%28x%29%2B2%5C%5C%5C%5Cg%28x%29%3Dx%2B5-2%3Dx%2B3)
Hence, the value of g(x) is x+3.
Answer:
x + 2 ( x - 20 )( 4 ) = -70
Step-by-step explanation:
hope this helps. . .<3
Answer: start at -3 on the graph then go up one to the right 4
Step-by-step explanation: